2012
DOI: 10.2215/cjn.05440611
|View full text |Cite
|
Sign up to set email alerts
|

Dialysate Sodium Concentration and the Association with Interdialytic Weight Gain, Hospitalization, and Mortality

Abstract: SummaryBackground and objectives Recommendations to decrease the dialysate sodium (DNa) prescription demand analyses of patient outcomes. We analyzed morbidity and mortality at various levels of DNa, simultaneously accounting for interdialytic weight gain (IDWG) and for the mortality risk associated with lower predialysis serum sodium (SNa) levels.Design, setting, participants, & measurements We used multiply-adjusted linear mixed models to evaluate the magnitude of IDWG and Cox proportional hazards models to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
112
4
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(133 citation statements)
references
References 40 publications
13
112
4
4
Order By: Relevance
“…DPNa + was superior to PPNa + in predicting IDWG%, predialysis diastolic, post-dialysis diastolic and mean arterial pressure (Table 3). This data is in contrast to a number of trials that suggest PPNa + to be more predictive [30,47,48]. Plasma Na + approaches Dial-Na + throughout hemodialysis, so intradialytic change in plasma Na + was predicted to be less than 3 mmol/L in our study, since Dial-Na + was randomized to be 3 mmol/L above (HIGHDialSOD) or below (LOWDialSOD) the SP.…”
Section: Discussioncontrasting
confidence: 70%
“…DPNa + was superior to PPNa + in predicting IDWG%, predialysis diastolic, post-dialysis diastolic and mean arterial pressure (Table 3). This data is in contrast to a number of trials that suggest PPNa + to be more predictive [30,47,48]. Plasma Na + approaches Dial-Na + throughout hemodialysis, so intradialytic change in plasma Na + was predicted to be less than 3 mmol/L in our study, since Dial-Na + was randomized to be 3 mmol/L above (HIGHDialSOD) or below (LOWDialSOD) the SP.…”
Section: Discussioncontrasting
confidence: 70%
“…This practice can lead to postdialysis hypernatremia that contributes to volume overload and increased BP (16). An increase of 0.17% of body weight for each additional 2 mmol/L dialysate sodium concentration has been reported (17). Reducing or individualizing dialysate sodium is now recommended as a means of improving control of sodium balance, volume, and BP in hypertensive patients on hemodialysis (16,18), and it has been shown to reduce IDWG and BP (19).…”
Section: Discussionmentioning
confidence: 99%
“…We have found that many facilities internationally use a single concentration of dialysate sodium, calcium, bicarbonate, or even potassium for nearly all patients, and that this single concentration varies between facilities (i.e., facilities choose one concentration or another). Recent DOPPS publications evaluating dialysate components, by IV analysis and other methods, have questioned the widespread belief that lower dialysate sodium levels are beneficial (47,48), and have raised the possibility that the commonly used dialysate potassium concentration of 2 mEq/L may raise the risk of sudden death compared with higher levels (41,49). Other analyses of dialysate composition are ongoing.…”
Section: Example: Dialysate Compositionmentioning
confidence: 99%